Performance analysis of a multi-format compatible all-optical data access method for satellite backbone-networks - Huang, Xinning; Shen, Yuerong; Song, Daming (Advanced Optical Technologies, 2026)
Optical inter-satellite links are a promising technology for constructing satellite backbone networks, owing to their high data transmission capacity and lightweight terminals. To circumvent the data-rate bottlenecks and structural complexity associated with optical-electrical-optical conversion, all-optical signal processing is essential. This paper addresses a common challenge at the relaying nodes of satellite backbone networks: handling concurrent access requests from multiple laser links. We propose and validate an all-optical data access system based on an optical time-lens. The system demonstrates robust performance and high modulation format compatibility. It successfully processes intensity-modulated, phase-modulated, and hybrid-format inputs entirely in the optical domain. The system’s reliability is further confirmed under practical conditions, including uneven wavelength spans and unequal data rates among the accessing links. It achieves bit-error rates below 10−7 and supports optical inter-satellite link transmission distances exceeding 4,500 km, even under hybrid modulation formats. With its simple structure and high compatibility, the proposed system offers a scalable solution for future multi-format satellite backbone networks.